Hablemos de lo que Duele. Prototipo de aplicación para aprender a regular las emociones en etapas de pre contemplación (2022)
With the objective of enriching the well-being of young people, providing them with information about their mental health status within a space of development and social interaction free of stigmas, the project Let's Talk About What Hurts, transforms depression into friendly monsters, which accompany the user to develop activities to regulate their emotions guiding them in the understanding, self-management, and identification of them.